Genome‐wide association analyses reveal the genetic basis of combining ability in rice. Issue 11 (29th April 2019) - Chen, Junxiao; Zhou, Hao; Xie, Weibo; Xia, Duo; Gao, Guanjun; Zhang, Qinglu; Wang, Gongwei; Lian, Xingming; Xiao, Jinghua; He, Yuqing
Summary: Combining ability is a measure for selecting elite parents and predicting hybrid performance in plant breeding. However, the genetic basis of combining ability remains unclear and a global view of combining ability from diverse mating designs is lacking. We developed a North Carolina II (NCII) population of 96 Oryza sativa and four male sterile lines to identify parents of greatest value for hybrid rice production. Statistical analyses indicated that general combining ability (GCA) and specific combining ability (SCA) contributed variously to different agronomic traits. In a genome‐wide association study (GWAS) of agronomic traits, GCA and SCA, we identified 34 significant associations ( P < 2.39 × 10 −7 ). The superior alleles of GCA loci ( Ghd8, GS3 and qSSR4 ) accumulated in parental lines with high GCA and explained 30.03% of GCA variance in grain yield, indicating that molecular breeding of high GCA parental lines is feasible. The distinct distributions of these QTLs contributed to the differentiation of parental GCA in subpopulations. GWAS of SCA identified 12 more loci that showed dominance on corresponding agronomic traits. We conclude that the accumulation of superior GCA and SCA alleles is an important contributor to heterosis and QTLs that greatly contributed to combining ability in our study would accelerate the identification of elite inbred lines and breeding of super hybrids.